Arte e ciência no renascimento : discussões e possibilidades de reaproximação a partir do Codex entre Cigoli e Galileo no século XVII - Silva, Josie Agatha Parrilha da (2013)
The research involves the relationship between Art and Science in the Renaissance from mature relationships between Galileo Galilei (1564-1642) and Lodovico Cardi (1559-1613), known as Cigoli. We initiated studies of this relationship from the Madonna Assunta painted by Cigoli in a fresco in the dome of Paolina's chapel in the Basilica Papale di Santa Maria Maggiore in Rome through the analysis of three primary sources: Sidereus nuncius ("The Starry Messenger") and Istoria and Dimostrazione sulle loro Macchie Solari and Accidenti, by Galileo Galilei, and the carteggio fra Cigoli and Galileo (exchange of correspondence between Cigoli and Galileo - with 31 letters translated at the unprecedented way in Brazil). The interest in research was born due to the extreme cartesian division experienced today, the beginning of XXI century, expressing the enormous gap between art and science, despite the existing proposals for interdisciplinary work in schools. The overall goal of the research was to understand the relationship between Art and Science, their approaches, distances, and epistemological and pedagogical implications from this understanding, rethinking proposed theoretical-practical rapprochement between them, as has happened in the Renaissance. We believe that by analyzing with unprecedented depth and the relationship between art and science from the work of Cigoli, its cratered moon, we can understand how this process took place and rethink the complexity of the issue of fragmented knowledge across today that we find in all levels of education. The main hypothesis raised is that the relationship art-science in the Renaissance could point out ways to make effective proposals for art and science and provide a transdisciplnary way again, this inseparable relationship, possibilities of organization and construction of new knowledge. If the science knowledge of Galileo were restricted to the impositions of the Church in the art this kind of things did not occur. By analyzing the image of the Madonna found in the fresco of Cigoli, representing the moon was no longer under the dictates of religious canons, but from a framework of a new science, beyond what the human eye could capture. The theoretical framework adopted for this research was the Phenomenology focusing on understanding and critical analysis of phenomena with appropriate and adapted to the science and art. Among the authors who gave theoretical support to this research, we highlight Husserl, Merleau-Ponty, among others. For image analysis we used the methodology proposed by Panofsky. As theoretical framework, beyond the work of Cigoli, we analyzed three primary sources: the Sidereus nuncius ("The Starry Messenger") and Istoria e Dimostrazione sulle Macchie Solari e loro Accidenti, Galileo Galilei, and carteggio fra Cigoli e Galileo (correspondence between Cigoli and Galileo - with 31 letters translated to portuguese). We used also authors from the fields of science and art, among these: Gombrich, Janson, Wolfflin, Read, Kuhn, Byington, Argan, Livio, Woortman. From the analysis of personal letters (translated into Portuguese for the first time here in its entirety), drawings and paintings, we can understand how it developed knowledge of both Galileo and Cigoli. The letters are part of a private correspondence between the two men. In these letters various issues are discussed, but the focus rested on the issues of the discoveries made by Galileo from the use of the telescope and watched by his friend Cigoli (Galileo was in Florence and Cigoli in Rome). The fresco of Cigoli remained largely hidden for centuries and was restored at the beginning of the 1930s. Today is exposed, as in 1613 - confirming that art is in line with science and that enables the construction of knowledge in different areas. Based on this understanding, the research contributed questions about theoretical and practical proposals of the rapprochement between Art and Science, as has occurred in the Renaissance.